Biotechnology for Tomorrow's World: Scenarios to Guide Directions for Future Innovation. Issue 5 (May 2021) - Cornelissen, Marc; Małyska, Aleksandra; Nanda, Amrit Kaur; Lankhorst, René Klein; Parry, Martin A.J.; Saltenis, Vandasue Rodrigues; Pribil, Mathias; Nacry, Philippe; Inzé, Dirk; Baekelandt, Alexandra
Abstract : Depending on how the future will unfold, today's progress in biotechnology research has greater or lesser potential to be the basis of subsequent innovation. Tracking progress against indicators for different future scenarios will help to focus, emphasize, or de-emphasize discovery research in a timely manner and to maximize the chance for successful innovation. In this paper, we show how learning scenarios with a 2050 time horizon help to recognize the implications of political and societal developments on the innovation potential of ongoing biotechnological research. We also propose a model to further increase open innovation between academia and the biotechnology value chain to help fundamental research explore discovery fields that have a greater chance to be valuable for applied research. Highlights: Identifying most relevant social, economic, and technological trends can help us understand in which direction future worlds could develop. Extrapolating long-term impact of current developments on the way we live may open avenues of biotechnology discovery research that would provide the starting basis for research and innovation addressing future needs. Maximizing innovation output in biotechnology requires a continuous cross-stakeholder interaction to timely share know–how obtained from discovery research in formats tailored to stakeholder use requirements